Research and Socio-Educational Impact Competences in the Degree Work of a University in Ecuador - Tinoco-Cuenca, Nasly Paquita (2020)
The purpose of this research is to evaluate the research competences and their impact on the relevance and socio-educational impact in the Undergraduate degree work of graduates of the education sciences career of a university in Ecuador. It is a basic research, because its results enrich the theoretical scientific knowledge; descriptive level and assumes the correlational design, because it establishes a relationship between two variables. The sample consisted of 55 Students, 05 Teachers, Two instruments were applied: a questionnaire to measure the variable Evaluation of research competencies, which consists of 25 items and measures the dimensions: about knowledge, content or knowledge, about knowing-being, behavior or attitudes and values, about knowing-doing, of skills, abilities or abilities; Another questionnaire to measure the variable relevance and socio-educational impact in the undergraduate degree work of graduates, which consists of 32 items and measures the dimensions: social relevance, work relevance and academic relevance, the instruments have been validated through expert judgment and they have an adequate level of reliability: 0.897 and 9.891 respectively. The results show that there is an incidence of the evaluation of the research competencesin the relevance and socio-educational impact of the undergraduate degree work of the graduates, reaches a level of 872.